An Important Milestone of Modern Urdu Naat: Abdul Aziz Khalid - Asif Ali Chatha (بازیافت, 2020)
Abdul Aziz khalid is a famous Urdu writer. His field of interest is Naat. He wrote poetry as well as prose. Especially he has created a special style in Naat which is an outcome of his vast and varied reading. This article presents a comprehensive and analytical study of his naat.